Given the function
To find g(4) - 3g(3)
Step 1: Find g(4)
g(4) is obtained by substituting 4 into the piecewise function for a range of x greater than or equal to 3
![\begin{gathered} \sin ce\text{ 4 }\ge3 \\ \text{then} \\ g(x)=x^4+x^2+x-3 \\ g(4)=4^4+4^2+4-3 \\ g(4)=256+16+4-3 \\ g(4)=273 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/r7jpsi2wlxtyzh6tf565lxop64udwyevgc.png)
Step 2: find 3g(3)
we will first find g(3)
g(3) is obtained by substituting 3 into the piecewise function for a range of x greater than or equal to 3
![\begin{gathered} \sin ce\text{ 3}\ge3 \\ \text{then} \\ g(x)=x^4+x^2+x-3 \\ g(3)=3^4+3^2+3-3 \\ g(3)=90 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/qrn7obullyqp6cvjgysx9xx4twcqfd54n2.png)
We can now find 3g(3)
![\begin{gathered} 3g(3)\text{ } \\ \text{simply means} \\ 3\text{ x g(3)} \\ where\text{ g(3)=90} \\ 3g(3)=3\text{ x 90 =270} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/1ak1kq8hhkivxggc567gfgorlvylxpn2ar.png)
Step 3: Find g(4) - 3g(3)
![\begin{gathered} g\mleft(4\mright)-3g\mleft(3\mright)=273-270 \\ g\mleft(4\mright)-3g\mleft(3\mright)=3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/2cijkrbsvycv26t2tyqwpadg74nfliz5uo.png)
Answer = 3